1977
DOI: 10.1177/001440297704300802
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Social Interaction/Withdrawal Assessment

Abstract: The purpose of this article is to review several practical and methodological issues related to the development of assessment instruments for child soc ial interaction and soc ial withdrawal. Specifically, the roles of (a) soc iometric peer rat ings, (b) behavioral observation measures . and (c) teacher ratings are discussed in relationship to their valid ity, reliability, and normative data characteristics. These measures are further discussed from the perspective of their usage in screening/identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
1
3

Year Published

1979
1979
1988
1988

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 42 publications
(42 reference statements)
1
25
1
3
Order By: Relevance
“…Unlike previous investigations, in which interaction rate was not associated with peer acceptance in younger populations (Deutsch, 1974;Gottman, 1977;Rosen, 1978, as cited in Asher et al, 1981Rubin, 1985), children identified as low frequency interactors were described as less well fiked, more disliked, and less enjoyable as playmates by their peers when compared to sociable children. The disparate findings of the present and previous studies suggest that social isolation may not affect sociometric status until children reach later developmental stages, perhaps when children are less commonly found to engage in solitary activities and are typically found to be more interactive (Greenwood, Walker, & Hops, 1977).…”
Section: Discussioncontrasting
confidence: 95%
“…Unlike previous investigations, in which interaction rate was not associated with peer acceptance in younger populations (Deutsch, 1974;Gottman, 1977;Rosen, 1978, as cited in Asher et al, 1981Rubin, 1985), children identified as low frequency interactors were described as less well fiked, more disliked, and less enjoyable as playmates by their peers when compared to sociable children. The disparate findings of the present and previous studies suggest that social isolation may not affect sociometric status until children reach later developmental stages, perhaps when children are less commonly found to engage in solitary activities and are typically found to be more interactive (Greenwood, Walker, & Hops, 1977).…”
Section: Discussioncontrasting
confidence: 95%
“…Despite this recognition, social skill development has been largely ignored from the standpoint of developing effective intervention procedures for those who are deficient in interpersonal behaviors (Greenwood, Walker, & Hops, 1977;Strain, Cooke & Apolloni, 1976).…”
mentioning
confidence: 99%
“…The system was developed to operate within a behavioral framework geared toward intervention by organizing a continuum of assessment functions. The system currently focuses on (1) screening of all children in a preschool class group, (2) identification of skill deficiency areas and determination of behavior change objectives, (3) frequent monitoring of intervention effects during a behavior change program, and (4) assessing effects at follow-up, after intervention (Cone and Hawkins, 1977;Greenwood et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…the measure in the natural setting, (3) the measure bears a substantial direct relationship to the behavior it predicts, (4) the instrument must be reliable, and (5) the instrument must be used in continuity with other assessment measures to complete problem definition, monitoring, and follow-up assessment functions essential to effective treatment (Greenwood et at., 1977;Hops and Greenwood, in press). The present study was designed to identify and evaluate screening measures for social withdrawal and limited social responsiveness in preschool children that could be effectively used by teachers.…”
mentioning
confidence: 99%
See 1 more Smart Citation